Global sex differences in personality: Replication with an open online dataset. Issue 3 (19th July 2019) - Kaiser, Tim; Del Giudice, Marco; Booth, Tom
Abstract: Objective: Sex differences in personality are a matter of continuing debate. In a study on the United States standardization sample of Cattell's 16PF (fifth edition), Del Giudice and colleagues (2012; PLoS ONE, 7, e29265) estimated global sex differences in personality with multigroup covariance and mean structure analysis. The study found a surprisingly large multivariate effect, D  = 2.71. Here we replicated the original analysis with an open online dataset employing an equivalent version of the 16PF. Method: We closely replicated the original MG‐MCSA analysis on N  = 21, 567 U.S. participants (63% females, age 16–90); for robustness, we also analyzed N  = 31, 637 participants across English‐speaking countries (61% females, age 16–90). Results: The size of global sex differences was D  = 2.06 in the United States and D  = 2.10 across English‐speaking countries. Parcel‐allocation variability analysis showed that results were robust to changes in parceling (U.S.: median D  = 2.09, IQR [1.89, 2.37]; English‐speaking countries: median D  = 2.17, IQR [1.98, 2.47]). Conclusions: Our results corroborate the original study (with a comparable if somewhat smaller effect size) and provide new information on the impact of parcel allocation. We discuss the implications of these and similar findings for the psychology of sex differences.